(untitled) (Indian Journal of Child Health, 2017)
Background: The neonates born to mothers with pregnancy-induced hypertension (PIH) are prone to have abnormalities in their umbilical cord blood hematology. However, the exact pattern of the derangements and their clinical correlations has not been defined. Objectives: The purpose of this study is to compare the hematological profile of cord blood of neonates born to mothers with and without PIH (gestational hypertension, pre-eclampsia, and eclampsia), and to evaluate short-term clinical outcomes in the two groups. Methods: A prospective case–control study was done on cord blood of 155 neonates born to mothers with PIH(cases) and compared with that of 155 neonates born to normotensive mothers (controls). 2 ml cord blood was collected at birth and was analyzed for - hemoglobin (Hb), various red cell indices including nucleated red blood cell (NRBC), reticulocyte count, total leukocyte count (TLC), differential leukocyte count, absolute neutrophil count (ANC), absolute lymphocyte count (ALC), platelet count, and cord blood smear examination. The cases and controls were followed up during their hospital stay for the clinical outcome. Results: The mean red cell distribution width, NRBC, and reticulocyte count in cases were 14.64±2.14%, 11.18±2.33/100white blood cells (WBCs) and 5.18±0.49% as compared with 11.84±0.78%, 4.32±1.32/100 WBCs, and 3.83±3.59% in controls (p<0.05). The mean TLC, ANC, and ALC in cases were 11642.70±6049.96/?L, 5682.30±2936.56/?L, 4955.91±2735.42/?L as compared with 13677.56±5711.14/?L, 6905.12±2932.99/?L, 6276.89±2649.98/?L in controls (p<0.05). The mean platelet count in cases was 164660.65±73817.05/?L as compared with 181148.39±60921.05/?L in controls (p<0.05). Erythrocyte changes were found in 78 (50.32%) cases and 44 (28.38%) controls (p<0.05).The relative risk (RR) of sepsis in PIH with respect to controls was>1 (1.64), with a significant increase in mortality as compared to controls. Conclusions: PIH increased the RR of sepsis (although not significantly) and mortality rate in the neonate, which can be related to cord blood hematological profile findings of leukopenia, absolute neutropenia, and thrombocytopenia, and increased NRBC count.